Fast‐Response, Highly Air‐Stable, and Water‐Resistant Organic Photodetectors Based on a Single‐Crystal Pt Complex - Periyanagounder, Dharmaraj; Wei, Tzu‐Chiao; Li, Ting‐You; Lin, Chun‐Ho; Gonçalves, Théo Piechota; Fu, Hui‐Chun; Tsai, Dung‐Sheng; Ke, Jr‐Jian; Kuo, Hung‐Wei; Huang, Kuo‐Wei; Lu, Norman; Fang, Xiaosheng; et al. (Advanced materials (Weinheim), 2020)
Organic semiconductors demonstrate several advantages over conventional inorganic materials for novel electronic and optoelectronic applications, including molecularly tunable properties, flexibility, low‐cost, and facile device integration. However, before organic semiconductors can be used for the next‐generation devices, such as ultrafast photodetectors (PDs), it is necessary to develop new materials that feature both high mobility and ambient stability. Toward this goal, a highly stable PD based on the organic single crystal [PtBr2(5,5′‐bis(CF3CH2OCH2)‐2,2′‐bpy)] (or “Pt complex (1o)”) is demonstrated as the active semiconductor channel—a material that features a lamellar molecular structure and high‐quality, intraligand charge transfer. Benefitting from its unique crystal structure, the Pt‐complex (1o) device exhibits a field‐effect mobility of ≈0.45 cm2 V−1 s−1 without loss of significant performance under ambient conditions even after 40 days without encapsulation, as well as immersion in distilled water for a period of 24 h. Furthermore, the device features a maximum photoresponsivity of 1 × 103 A W−1, a detectivity of 1.1 × 1012 cm Hz1/2 W−1, and a record fast response/recovery time of 80/90 µs, which has never been previously achieved in other organic PDs. These findings strongly support and promote the use of the single‐crystal Pt complex (1o) in next‐generation organic optoelectronic devices. A Pt‐complex‐based organic semiconductor is developed as the active channel and/or photoabsorption layer for high‐performance organic device applications. The Pt‐complex device displays a stable mobility (0.45 cm2 V−1 s−1), a remarkable photoresponsivity (1000 A W−1), and a record fast response/fall time (80/90 µs), demonstrating the highest combined efficiency and stability reported for an organic semiconductor.